Bullied by Siblings and Peers: The Role of Rejecting/Neglecting Parenting and Friendship Quality Among Korean Children - Kim, Jingu; Kim, Eunha (Journal of Interpersonal Violence, 2019)
The primary aim of this study was to examine the direct and indirect links of rejecting/neglecting parenting, sibling victimization, and friendship quality with peer victimization using a convenience sample of 584 Korean children in Grades 3 to 6. In addition, we tested whether these associations differed between male and female students. Structural equation modeling was performed to analyze the data. The results revealed rejecting/neglecting parenting indirectly influenced peer victimization through sibling victimization for both males and females, although such effects were stronger for females than males. Sibling victimization had a direct effect on peer victimization across both sexes, although it indirectly influenced peer victimization through poor friendship quality only for males. Therefore, bullying prevention and intervention programs must involve parents to make them aware of the important role they play in this process and to improve their parenting styles and involvement in sibling conflicts. Furthermore, while the role of friendship quality needs to be highlighted to prevent peer victimization among males, future research continues to explore other peer variables that are related to decreased peer victimization for females.
Keywords: Adolescent; Aggression; Bullying; Child; Crime Victims; Female; Friends; Humans; Male; Parent-Child Relations; Parenting; Parents; Peer Group; Republic of Korea; Siblings; friendship quality; peer victimization; rejecting/neglecting parenting; sibling victimization